Risk Factors Associated with Mother-to-Child HIV Transmission in Wukari Local Government Areas (LGAs), Taraba State - Bature, Gambo Innga (Mikailalsys Journal of Mathematics and Statistics, 2025)
Mother-to-child transmission (MTCT) of HIV continues to pose a major public health concern in Nigeria, particularly in sub-Saharan Africa. This study investigated the factors influencing MTCT of HIV in Wukari Local Government, Taraba State, using secondary data from 550 nursing mothers attending the General Hospital. A cross-sectional design was adopted, with chi-square tests used to assess associations between MTCT and maternal characteristics, while binary logistic regression identified predictors of transmission. The MTCT rate was 11.5% (63/550). Chi-square analysis revealed significant associations with maternal age (χ² = 8.181, p = 0.017), mode of delivery (χ² = 68.469, p < 0.001), maternal education (χ² = 12.729, p = 0.005), and antenatal care (ANC) visits (χ² = 36.672, p < 0.001). Logistic regression showed that mothers aged 25–35 years (OR = 3.299) and above 35 years (OR = 3.930) had higher odds of transmission than those under 25. Caesarean delivery markedly increased transmission risk (OR = 15.964), while ANC visits were unexpectedly associated with higher odds (OR = 12.851). Higher maternal weight appeared protective (OR = 0.951). The findings demonstrate that maternal age, delivery mode, and ANC patterns are significant determinants of MTCT of HIV. Targeted interventions are needed for older mothers and to strengthen prevention strategies, particularly in the context of caesarean deliveries, to reduce transmission rates and improve maternal–child health outcomes.